Dampak Ratifikasi Indonesia Terhadap International Convention for the Suppression of Terrorist Bombings 1997 - Golda C L Ingratubun; Lucia Charlota Octovina Tahamata; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Terrorism as a type of Activities of Transnational/Criminal Organizations is a feared crime because it threatens the sovereignty of the state, society and individuals, disrupts national stability and pollutes democratic values.Purposes of the Research: To study and find out what things are regulated in the 1997 International Convention for the Suppression of Terrorist Bombings and the impact of Indonesia ratifying the 1997 International Convention for the Suppression of Terrorist Bombings. Methods of the Research: This study uses a normative juridical type which conducts research on the rules, norms and legal principles based on laws and regulations relating to the problem under study.Results of the Research: The results of this study explain the matters regulated in the 1997 International Convention for the Suppression of Terrorist Bombings, namely the efforts deemed necessary by the state party in tackling terrorism crimes within the scope of its country. It also regulates mutual legal assistance cooperation efforts, where countries that build cooperative relations can exchange information about the movement of terrorists considering that terrorism is a trans-national crime so that its handling can be more effective. The jurisdiction referred to in this convention is the regulation concerning the authority to enforce national law in the territory of a party based on the laws and regulations of that country. Extradition referred to in this convention is a regulation regarding the process of surrendering a person who is suspected or convicted to a country requesting surrender because he has committed a crime outside the territory of the surrendering country.